Mapping Io's Surface Composition With Juno/JIRAM. Issue 11 (13th November 2020) - Tosi, F.; Mura, A.; Lopes, R. M. C.; Filacchione, G.; Ciarniello, M.; Zambon, F.; Adriani, A.; Bolton, S. J.; Brooks, S. M.; Noschese, R.; Sordini, R.; Turrini, D.; et al.
Abstract: The surface composition of Io is dominated by SO2 frost, plus other chemical species identified or proposed over the past decades by combining Earth‐based and space‐based observations with laboratory data. Here we discuss spectroscopic data sets of Io obtained by the Jovian InfraRed Auroral Mapper (JIRAM) spectro‐imager onboard Juno in nine orbits, spanning a 3‐year period. We display average spectral profiles of Io in the 2–5 μm range, and we use band depths derived from those profiles to map the geographic distribution of SO2 frost and other spectral features. This data set allows for an ~22% surface coverage at 58 to 162 km/px and in a broad range of latitudes. Our results confirm the broadly regional SO2 ‐frost trends already highlighted by Galileo/NIMS. Io's average spectral profiles as well as the mapping of the 4.47‐μm band also confirm that SO2 exists in the 32 S 16 O 18 O isotopic form. Surprisingly, the mapping performed by JIRAM shows that the absorption band at 2.1 μm is unrelated to SO2 frost, while we map for the first time the depth of the 2.65‐μm band, highlighting regions enriched in this absorber, possibly H2 S. JIRAM data confirm that the 3.92‐μm band, likely due to Cl2 SO2, is largely related to the SO2 distribution. The correlation between Cl2 SO2 and ClSO2, possibly revealed at 4.62 μm, is not equally clear. The simultaneous presence of two very weak spectral features at 4.55 and 4.62 μm suggests that nitrile compounds or tholins may also be present on the surface. Plain Language Summary: The surface of Io is mainly covered by sulfur dioxide (SO2 ) frost and by other chemical species. The Jovian InfraRed Auroral Mapper (JIRAM) instrument onboard the NASA Juno spacecraft, in orbit around Jupiter, can occasionally observe the Galilean satellites through its slit spectrometer (2–5 μm range). We show average spectral profiles of Io obtained by JIRAM in a 3‐year period, mapping the geographic distribution of SO2 frost and other spectral features. Our results confirm the broadly regional SO2 ‐frost trends already highlighted in the past. Our data confirm that SO2 exists in multiple isotopic forms. Surprisingly, the mapping performed by JIRAM shows that the absorption band at 2.1 μm is unrelated to SO2 frost. We map for the first time the depth of the 2.65‐μm band, which might be related to hydrogen sulfide (H2 S). We also highlight regions enriched in this absorber. We confirm that the 3.92‐μm band, ascribed to sulfuryl chloride (Cl2 SO2 ), is largely correlated with the SO2 distribution. The correlation between Cl2 SO2 and ClSO2, possibly revealed at 4.62 μm, is not equally clear. The simultaneous presence of two very weak spectral features at 4.55 and 4.62 μm suggests that nitrile compounds or tholins may also be present on the surface. Key Points: We use spectra acquired by Juno/JIRAM in the range 2–5 μm over a 3‐year period, covering ~22% of Io, to map its surface composition The 2.1‐μm band and the 2.65‐μm band are unrelated with SO2 frost but display trends possibly related to the transport of volatiles We confirm that the 4.47‐μm band is diagnostic of 32 S 16 O 18 O, and we show that ClSO2 is not everywhere linked to the abundance of Cl2 SO2